Exploratory data analysis using R - Pearson, Ronald K. (Boca Raton FL : CRC Press/Taylor & Francis Group, 2018)
"This textbook will introduce exploratory data analysis (EDA) and will cover the range of interesting features we can expect to find in data. The book will also explore the practical mechanics of using R to do EDA. Based on the author's course at the University of Connecticut, the book assumes no prior exposure to data analysis or programming, and is designed to be as non-mathematical as possible. Exercises are included throughout, and a Solutions Manual will be available. The author will also provide a supplemental R package through the Comprehensive R Archive Network that will include implementations of some of the features in this book, along with data examples, tools, and datasets"--
"A CRC title, part of the Taylor & Francis imprint, a member of the Taylor & Francis Group, the academic division of T&F Informa plc."
Keywords: Data mining -- Computer programs; R (Computer program language); Electronic data processing--Data preparation; Mathematical statistics--Data processing